Daily Monitoring of Emotional Responses to the Coronavirus Pandemic in Serbia: A Citizen Science Approach - Sadiković, Selka; Branovački, Bojan; Oljača, Milan; Mitrović, Dušanka; Pajić, Dejan; Smederevac, Snežana (Frontiers in Psychology, 2020)
The COVID-19 pandemic, a health emergency with international consequences, has brought serious impact on all aspects of society and affects not only health and economy, but psychological functioning and mental health as well. This research was conducted in order to examine and further our understanding of emotional reactions to the ongoing pandemic. Change in emotional reactions during the pandemic and relations with specific pandemic related behaviors and personality traits from the revised Reinforcement sensitivity theory were explored. The research was conducted in Serbia for 35 days while the country was in a state of emergency, as a citizen science project. Out of the 1526 participants that joined the study, 444 (67% female) had measures for all five weeks. Longitudinal changes in four emotional states during the pandemic were examined: worry, fear, boredom, and anger/annoyance. Results indicate a decrease in all four emotional states over time. The biggest decrease was present in case of worry, followed by fear and boredom. Regression analysis showed that personality dimensions, as well as behavioral responses in this situation significantly predicted emotional reactions. Findings revealed the Behavioral activation system was significantly related to worry, fear and boredom, Fight with boredom and anger, and the Behavioral inhibition system with anger. Adherence to protection measures, as well as increased exposure to the media, had significant positive relations with worry and fear. These results indicate that both stable characteristics and specific pandemic-related behaviors are significantly related to emotional response during the pandemic.